Terveysalan opiskelijoiden oppimiskokemuksia etäsimulaatiosta. - Silén-Lipponen, Marja; Saukkonen, Mirja; Äijö, Marja (Tutkiva Hoitotyö / Nursing Evidence, 2025)
Purpose of the Study: To investigate the experiences of healthcare students with remote simulation. The study piloted an online implementation of remote simulation, two different hybrid implementations, and a learning task implementation. Materials and Methods: The research data was collected from 69 health-care students using a questionnaire that included multiple-choice and open-ended questions, as well as an open form. Quantitative data was analyzed using frequencies and percentages, and qualitative data using inductive content analysis. Results: Students' willingness to participate in remote simulation and encouraging teacher guidance promoted learning in remote simulations. Technical challenges and scenario deficiencies hindered learning in remote simulations. Conclusions: In remote simulations, learning is promoted by careful planning as well as the teacher's technical and pedagogical expertise. Compatible content and the implementation model of the remote simulation promote learning that aligns with the simulation's objectives. Teachers need training in engaging students and managing technologies during remote simulations. Supporting students and providing instructions for using remote technology engages them in a new way of learning.